Why Theists Cannot Accept Skeptical Theism - Piper, Mark (Sophia, 2008)
In recent years skeptical theism has gained currency amongst theists as a way to escape the problem of evil by invoking putatively reasonable skepticism concerning our ability to know that instances of apparently gratuitous evil are unredeemed by morally sufficient reasons known to God alone. After explicating skeptical theism through the work of Stephen Wykstra and William Alston, I present a cumulative-case argument designed to show that skeptical theism cannot be accepted by theists insofar as it crucially undermines epistemic license to the very theism it is invoked to defend. I also argue that attempts to defend a theism-friendly moderate version of skeptical theism either fail to halt the spread of damaging skepticism, or lack philosophical validity.